A Kinetic Study of Marginal Soil Energy Plant Helianthus annuus Stalk Pyrolysis. (4th February 2013) - Yan, Huaxiao; Zhao, Hui; Zhang, Yan; Tian, Yuanyu; Xie, Kechang
Abstract : The pyrolytic characteristics and kinetics of new marginal soil energy plant Helianthus annuus stalk were investigated using thermogravimetric (TG) method from 50 to 800°C in an inert argon atmosphere at different heating rates of 5, 10, 20, and 30°C min −1 . The kinetic parameters of activation energy and pre-exponential factor were deduced by Popescu, Flynn-Wall-Ozawa (FWO), and Kissinger-Akahira-Sunose (KAS) methods, respectively. The results showed that three stages appeared in the thermal degradation process. The primary devolatilization stage of H. annuus stalk can be described by the Avrami-Erofeev function( n = 4 ) . The average activation energy of H. annuus stalk was only 142.9 kJ mol −1 . There were minor kinetic compensation effects between the pre-exponential factor and the activation energy. The results suggest that H. annuus stalk is suitable for pyrolysis, and more importantly, the experimental results and kinetic parameters provided useful information for the design of pyrolytic processing system using H. annuus stalk as feedstock.